Hidradenitis suppurativa gains increasing interest on World Wide Web: a source for patient information?. (21st March 2017) - Hessam, Schapoor; Salem, Johannes; Bechara, Falk G.; Haferkamp, Axel; Heidenreich, Axel; Paffenholz, Pia; Sand, Michael; Tsaur, Igor; Borgmann, Hendrik
Abstract: Background: Gathering health information from Internet websites is increasingly utilized by patients. No data exist about hidradenitis suppurativa (HS)‐related online health information. Thus, we aimed to study the quality, popularity, readability, and timeliness of the most frequented websites on HS. Methods: Google Trends was used to evaluate the public interest in HS. An Internet search on Google was performed for the terms "hidradenitis suppurativa, " "acne inversa, " and "Verneuil's disease." Readability scores, HONcode quality certification, Alexa popularity rank, and content were assessed. Results: Google search queries on HS have steadily risen in the last 10 years. The website analysis revealed 39 unique websites, which were difficult to read. Ten websites (26%) had HONcode quality certification, and the median (IQR) Alexa popularity rank was 48871 (2333–361275). Thirteen websites (33%) yielded disease‐specific photos with a median rating between "quite useful" and "uncertain." A therapy option with adalimumab was mentioned on 11 websites (28%). Conclusions: In addition to an increasing interest, we found a broad variation in the quality, readability, popularity, and timeliness of content on HS‐related websites. Improvement of the quality and readability of HS‐related websites is desirable to potentially raise disease awareness and contribute to an earlier presentation of patients suffering with undiagnosed HS.